West Nile Virus Infection - Llorente, Francisco (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint covers different aspects of the West Nile virus (WNV), a mosquito-borne pathogen that belongs to the Flavivirus genus (family Flaviviridae). The virus is maintained in nature in a rural cycle between mosquito vectors, mainly Culex species, and avian hosts. Spillover from this cycle occasionally results in outbreaks in horses and humans. In severe cases, the infection can induce neurological signs, such as meningitis and encephalitis, and in some cases, it can lead to death. The virus has spread across the world in this century, including its expansion in the Americas since 1999, and an increase in the number of outbreaks and its severity has been observed in Europe in recent years. Considering all these aspects, an approach including public, animal and environmental health is the best option to increase the knowledge of this problem, making this disease an excellent example of a "One Health" issue. Bearing in mind this multidisciplinary aspect, the volume includes contributions related to the pathogenesis, vaccines, diagnosis and epidemiology of the virus both in humans and animals.